1975
DOI: 10.1007/bf00132919
|View full text |Cite
|
Sign up to set email alerts
|

Seed protein electrophoresis of the wild and cultivated species of selection faba of Vicia

Abstract: The seed protein profile obtained by disc electrophoresis was found to be a diagnostic characteristic of the broad bean, V.jaba, and of its taxonomically wild relatives V. narbonensis, V. galilaea and V. hyaeniscyamus The marked difference in the seed protein profile of the cultivated species and the three wild species indicated that none of the latter can be considered as the wild progenitor of V. faba. The similarity in the profiles of V. galilaea and V. hyaeniscyamus was consistent with the morphological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 12 publications
4
17
0
Order By: Relevance
“…From the comparison of the electrophoretic bands at the different levels considered (populations, groups of populations from different geographical origin and groups of populations belonging to different botanical varieties), we can conclude that ; (1) The populations studied do not seem to be very distant from each other whichever the method (Jaccard's coefficients or PCA) used to estimate the distances . This result agrees with those found by other researchers who have studied the A intraspecific biochemical variation of Vicia faba (Bassiri & Rouhani, 1977 ;Ladizinsky, 1975b ;Abdalla & Gunzel, 1979 ;Gates & Boulter, 1980;Stegemann et al ., 1980) . (2) The analysis performed at the varietal level showed that three botanical varieties (major, equina and minor) were very close to each other ; Ladizinsky (1975b), Abdalla & Gunzel, (1979) and Fayed (1989) found no differences among these botanical varieties in terms of biochemical variation .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…From the comparison of the electrophoretic bands at the different levels considered (populations, groups of populations from different geographical origin and groups of populations belonging to different botanical varieties), we can conclude that ; (1) The populations studied do not seem to be very distant from each other whichever the method (Jaccard's coefficients or PCA) used to estimate the distances . This result agrees with those found by other researchers who have studied the A intraspecific biochemical variation of Vicia faba (Bassiri & Rouhani, 1977 ;Ladizinsky, 1975b ;Abdalla & Gunzel, 1979 ;Gates & Boulter, 1980;Stegemann et al ., 1980) . (2) The analysis performed at the varietal level showed that three botanical varieties (major, equina and minor) were very close to each other ; Ladizinsky (1975b), Abdalla & Gunzel, (1979) and Fayed (1989) found no differences among these botanical varieties in terms of biochemical variation .…”
Section: Discussionsupporting
confidence: 83%
“…This result agrees with those found by other researchers who have studied the A intraspecific biochemical variation of Vicia faba (Bassiri & Rouhani, 1977 ;Ladizinsky, 1975b ;Abdalla & Gunzel, 1979 ;Gates & Boulter, 1980;Stegemann et al ., 1980) . (2) The analysis performed at the varietal level showed that three botanical varieties (major, equina and minor) were very close to each other ; Ladizinsky (1975b), Abdalla & Gunzel, (1979) and Fayed (1989) found no differences among these botanical varieties in terms of biochemical variation .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations